2005
DOI: 10.1088/0953-8984/17/10/023
|View full text |Cite
|
Sign up to set email alerts
|

Transparent Cr-doped SnO2thin films: ferromagnetism beyond room temperature with a giant magnetic moment

Abstract: Laser ablated Cr-doped SnO 2 thin films grown on various kinds of substrates all show ferromagnetism well beyond room temperature. Surprisingly, films of Sn 0.95 Cr 0.05 O 2 grown on LaAlO 3 substrates have a giant magnetic moment of 6 µ B /Cr, which is 20-30 times larger than that of films grown under the same conditions on SrTiO 3 and R-cut sapphire substrates. All films are highly transparent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
62
0
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 140 publications
(65 citation statements)
references
References 13 publications
2
62
0
1
Order By: Relevance
“…Tin dioxide layers doped with antimony or iron ions are used in electroluminescent devices [6,7]. Doping a small amount of a transition metal (Fe, Cr, Co, Ni, V) into non-magnetic oxides could induce room temperature ferromagnetism, indicating the potential of such systems for spintronic applications [8][9][10][11][12][13][14][15][16]. Combinations of various semiconductors (SnO 2 , TiO 2 , ZnO) and noble metals (Ag, Au, Pd and Pt) boost photocatalytic activity by trapping photo-induced charge-carriers and improving charge transfer process [1-3, 15, 16].…”
Section: Introductionmentioning
confidence: 99%
“…Tin dioxide layers doped with antimony or iron ions are used in electroluminescent devices [6,7]. Doping a small amount of a transition metal (Fe, Cr, Co, Ni, V) into non-magnetic oxides could induce room temperature ferromagnetism, indicating the potential of such systems for spintronic applications [8][9][10][11][12][13][14][15][16]. Combinations of various semiconductors (SnO 2 , TiO 2 , ZnO) and noble metals (Ag, Au, Pd and Pt) boost photocatalytic activity by trapping photo-induced charge-carriers and improving charge transfer process [1-3, 15, 16].…”
Section: Introductionmentioning
confidence: 99%
“…6 Hence, SnO 2 has gained attraction for applications in solar cells, heat mirrors, catalysis, and gas sensing applications. Recent experimental reports on transition metal (TM)-doped (V, 7 Cr, 8 Mn, 9 Fe, 10 Co, 11 Ni, 12 Cu, 13 and Zn 14 ) SnO 2 have shown promising application on the high temperature ferromagnetic semiconductors. Theoretical and computational studies on the TM-doped (Co, 15 Mn, 16 Ni, 17 Cu, 18 and Zn 19,20 ) SnO 2 have also been performed to understand the induced magnetism.…”
mentioning
confidence: 99%
“…Among these high T C compounds, a promising but less studied material is TM doped-SnO 2 , which evoked a lot of attention when S. B. Ogale et al 4 found a giant magnetic moment ͑GMM͒ in Co-doped SnO 2 . Following this discovery, TM doped-SnO 2 has been extensively studied experimentally [5][6][7] and theoretically. [8][9][10][11] Very recently, 12 we investigated the origin of GMM in doped SnO 2 .…”
mentioning
confidence: 99%